2013
DOI: 10.1016/j.pain.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance develops to the antiallodynic effects of the peripherally acting opioid loperamide hydrochloride in nerve-injured rats

Abstract: Peripherally acting opioids are potentially attractive drugs for the clinical management of certain chronic pain states due to the lack of centrally mediated adverse effects. However, it remains unclear whether tolerance develops to peripheral opioid analgesic effects under neuropathic pain conditions. We subjected rats to L5 spinal nerve ligation (SNL) and examined the analgesic effects of repetitive systemic and local administration of loperamide hydrochloride, a peripherally acting opioid agonist. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Therefore, we used the modified “Chung” model (L5 SNL), in which the nerve injury is standardized and limited to L5 (Guan et al, 2010b; He et al, 2013), to investigate the respective effects of SNL on injured and adjacent uninjured DRGs at various post-injury time points. We chose rats for this set of experiments because L5 SNL is easier to perform in rats than in mice, and more DRG tissue can be harvested from rats.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used the modified “Chung” model (L5 SNL), in which the nerve injury is standardized and limited to L5 (Guan et al, 2010b; He et al, 2013), to investigate the respective effects of SNL on injured and adjacent uninjured DRGs at various post-injury time points. We chose rats for this set of experiments because L5 SNL is easier to perform in rats than in mice, and more DRG tissue can be harvested from rats.…”
Section: Resultsmentioning
confidence: 99%
“…MOR at the peripheral nerve terminals in the skin, along the nociceptor axons, or at the nociceptor cell body). Note, however, that repeated intradermal administration of MOR agonists 23 , which arguably only act on MOR at nociceptor peripheral terminals, or chronic administration of the peripherally acting opioid loperamide 48 is sufficient to induce OIH and/or antinociceptive tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study suggested that repeated use of loperamide for alleviating neuropathic mechanical hypersensitivity may lead to the development of tolerance, possibly at peripheral opioid receptors. 51 Because different MOR agonists induce different magnitudes of receptor internalization, desensitization, and tolerance processes, it remains to be tested whether DALDA leads to the development of analgesic tolerance or opioid-induced hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%